Determining types of treatment to be adopted by patients with type 2 diabetis mellitus in a primary care setting: A grounded theory approach / Low Lee Lan - Low , Lee Lan (2016)
Diabetes mellitus is a multi-faceted chronic illness which involves a life-long treatment process that requires patients to continuously engage with the healthcare system. Understanding how patients with diabetes manoeuvre through the current healthcare system for treatment is critical in assisting patients in disease management optimisation. This study aims to explore the issues that determine type 2 diabetic patient‘s decision in selecting treatment strategy and the decision-making process in deciding upon their treatment options. The ultimate goal of this study is to develop a substantive theoretical model which explains the treatment strategy adopted by patients with type 2 diabetes mellitus in a primary care setting. A grounded theory approach was used to answer the research questions. Twelve patients diagnosed with type 2 diabetes mellitus, nine family members of some of the patients and five healthcare providers from the primary care clinics were interviewed using a semi-structured interview guide. Three focus group discussions were conducted among thirteen healthcare providers from public primary care clinics. The concept of ―experimentation‖ was observed in patient‘s decision-making for adopting their treatment strategy. This ―experimentation‖ process required triggers followed by information-seeking related to treatment characteristics from entrusted family members, friends, and healthcare providers to enable decision-making related to the choice of treatment modalities. The entire process was dynamic and iterative through interactions with the healthcare system. The decision-making process related to choosing treatment types was complex and exhibited a trial-and-error approach. The purpose of this process was to fulfil a patient‘s expected outcome or personal goal. The determinant factors illustrated in this model are more diverse than earlier health-seeking behaviour models. This study suggests that an element of uniqueness exists in patients, since individual experiences with regard to symptoms and complications are unique to each patient. The experimentation process is iv seen as one that reflects the experiential learning element where learning is accomplished through the action of testing one new treatment with a strategy and this phenomenon is reflective of the concept of adult learning. This model underlines the importance of providing diabetic patients with a safe environment to experiment different treatments within the current healthcare system. Denying patients this experimental trial-and-error process could potentially produce negative consequences such as patients experiencing unmet needs, which could result in patients turning to alternative treatment modalities or switching healthcare providers. Patients should be encouraged to share their treatment strategy with their healthcare providers. Simultaneously, healthcare providers could encourage patients to verify any new information received from sources other than medical experts. This would avoid the perception of risk and subsequently prevent risky behaviour in diabetes management by patients. In conclusion, the substantive theoretical model generated from this study is abstract and believed to possess broader applicability to other diseases.